Economic Burden of ESRD to the Malaysian Health Care System - Ismail, Hirman; Abdul Manaf, Mohd Rizal; Abdul Gafor, Abdul Halim; Mohamad Zaher, Zaki Morad; Ibrahim, Adriana Irawati Nur (Elsevier, 2019)
Introduction: Prevalence of chronic kidney disease (CKD) in Malaysia is 9.07% of the total population, of which 0.36% are at stage 5 CKD or end-stage renal disease (ESRD). Public-private partnership has improved accessibility of renal replacement therapies (RRT), especially dialysis, in Malaysia, but the economic burden of the existing RRT financing mechanism, which is predominantly provided by the public sector, has never been quantified. Methods: Primary data were collected through a standardized survey, and secondary data analysis was used to derive estimates of the ESRD expenditure. Results: Total annual expenditure of ESRD by the public sector has grown 94% within a span of 7 years, from Malaysian Ringgit [MYR] 572 million (US dollars [USD] 405 million, purchasing power parity [PPP] 2010) in 2010 to MYR 1.12 billion (USD 785 million, PPP 2016) in 2016. The total ESRD expenditure in 2010 constituted 2.95% of the public sector's total health expenditure, whereas in 2016, the proportion has increased to 4.2%. Only 6% of ESRD expenditure was spent on renal transplantation, and the remaining 94% was spent on dialysis. Conclusion: The share of ESRD expenditure in total health expenditure for the public sector is considered substantial given only a small proportion of the population is affected by the disease. The rapid increase in expenditure relative to the national total health expenditure should warrant the relevant authorities about sustainability of the existing financing mechanism of ESRD and the importance to institutionalize more drastic preventive measures. © 2019 International Society of Nephrology